C-Axis-penetrated mesoporous MWW zeolite nanosheets: preparation by H2O2-induced micro-explosion and their enhanced properties. Issue 16 (27th June 2022) - Zhang, Chunna; Lin, Feng; Kong, Lingtao; Ye, Zhaoqi; Pan, Di; Li, Hongbin; Li, He; Liu, Peng; Zhang, Yahong; Zhang, Hongbin; Tang, Yi
Abstract : A series of highly dispersed and c -axis-penetrated mesoporous MWW oligolayers with enhanced properties was prepared via an efficient, green, and controllable method through H2 O2 -induced micro-explosion. Abstract : Zeolite nanosheets are a burgeoning class of two-dimensional (2D) nanomaterials due to their fascinating properties and diverse applications. However, the effective and controllable preparation of advanced 2D zeolite materials with hierarchical structure and enhanced properties still needs to be investigated. Here, we report highly dispersed oligolayer MWW nanosheets ( ca. 2–4 layers) with c -axis-penetrated mesopores, prepared by H2 O2 -induced micro-explosion coupled with ethanolamine pre-treatment from the multilayered precursor MCM-22P. The vertically aligned mesopores are well merged with intrinsic microporosity within MWW oligolayers with structural integrity. Meanwhile, the removal of OSDA and surface-grafted ethanolamine can be simultaneously achieved apart from the construction of the hierarchical structure. The porosity can be easily regulated by adjusting the H2 O2 content, while the framework structure, composition, and intrinsic acidity are retained. Furthermore, benefiting from the greatly improved accessibility of intralayer 10-MR sinusoidal channels, the c -axis-penetrated mesoporous MWW zeolite nanosheet shows enhanced adsorption/diffusion properties and catalytic performances for bulky substrate conversion. This work provides a synergetic post-treatment method for the more rational and controllable design and application of novel layered hierarchical zeolite catalysts, and the efficient and versatile approach reported here shows great potential for industrial applications.